(untitled) (Bangladesh Journal of Zoology, 2015)
Proximate composition and microbial quality of three aquarium fish feeds commonly found in Bangladesh were collected from fish feed market of Dhaka city. Significantly higher moisture content (2.12 ± 0.06%) was found in Super NovaTM fish feed while similar moisture content was detected in other two feeds (p<0.05). On the other hand ash content detected in OptimumTM and Osaka 2000TM aquarium fish feed was significantly higher than that of Super NovaTM (10.67±0.19%) (p<0.05).Protein content found in OptimumTM (42.21 ± 0.12%) was significantly higher than that of Osaka 2000TM and Super NovaTM (p<0.05). However, similar lipid content was found in OptimumTM (1.06 ± 0.03%) and Super NovaTM (1.13 ± 0.01%) aquarium fish feed which were significantly higher than that of Osaka 2000TM (p<0.05). The Escherichia coli and Staphylococcus aureus were found in all feeds. However Vibrio sp was not found in any feed. Total bacterial count was significantly higher in Osaka 2000TM feed than that of others (P<0.05). However S. aureus was significantly higher in Super NovaTM than that of others while E. coli count was significantly higher in OptimumTM fish feed than that of others (p<0.05). Nutritional quality of the aquarium fish feed was qualified to some extent to meet the minimum requirement of the aquarium fish while microbial quality indicates some degrees of deterioration which may cause diseases of the aquarium fishes. Thus proper storage condition, hygienic handling and processing should be maintained to prevent the microbial contamination in aquarium fish feeds. There should be a monitoring cell from the government to assess the quality of this expensive imported feeds for aquarist. Bangladesh J. Zool. 42(2): 283-294, 2014